13lnx-7=0

Simple and best practice solution for 13lnx-7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13lnx-7=0 equation:


Simplifying
13lnx + -7 = 0

Reorder the terms:
-7 + 13lnx = 0

Solving
-7 + 13lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 13lnx = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 13lnx = 0 + 7
13lnx = 0 + 7

Combine like terms: 0 + 7 = 7
13lnx = 7

Divide each side by '13nx'.
l = 0.5384615385n-1x-1

Simplifying
l = 0.5384615385n-1x-1

See similar equations:

| 13x-1/3x+9=4 | | (-6.0)+(-3.2)= | | 15-27=15 | | (7.5)-(12.3)= | | X-60=5x | | (-0.25)+(0.41)= | | (-18.1)+(10.9)= | | -10=-14v+14v+3 | | 10(1+3b)=-20+3b | | 15=(2.5x)/2 | | 5.7+0.8x=0.9 | | (-5.5)-(-8.7)= | | 3(4x-2.4)=5x-7.2 | | 20/2(5*5)=x | | 2k^2+6=4k | | (-3.8)+(0.13)= | | 3y/5=37-4 | | 4.7+0.05x=5.09 | | 7.1=10x+1.5 | | Ln(x-1)+Ln(3)=Lnx | | (x+1)+(x-1)=45 | | f=4.135135 | | 10log(1/4) | | -0.1(4x+1)-3.5x= | | 3m+(m-10)=180 | | 5*2x=40 | | 3+(9+3)=-3(-3*-24) | | x^2+6x+18=12 | | 5y+6=3y-9 | | h=-1.7t^2+3.5 | | 13x-81+92=360 | | x^2+6x+6=12 |

Equations solver categories